2018
DOI: 10.4314/ijbcs.v12i3.6
|View full text |Cite
|
Sign up to set email alerts
|

Multiplication végétative de <i>Cola acuminata</i> (Pal. de Beauv.) Schott & Endlicher par marcottage à Kisangani, République Démocratique du Congo

Abstract: » qui à travers son projet « AFTP4A » a soutenu financièrement les travaux de recherche. RESUME A Kisangani, le kolatier, Cola acuminata est utilisé à des fins thérapeutiques et sociales et procure des revenus non négligeables aux personnes impliquées dans sa filière. Les produits de kolatier (noix, écorce, feuille) sont obtenus par des récoltes en forêt qui est pourtant menacée. Sa domestication est une nécessité. La présente étude avait pour objet de déterminer le diamètre et l'orientation des branches pour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…In the present study, bud regeneration rate was generally low. Paluku et al [19] made the same observations during in vitro regeneration of Cola acuminata. This study revealed that the production of friable, greenish callus in the two local varieties tested auguring a prospect for intense proliferation through regeneration of neoformed organogenesis callus.…”
Section: Discussionmentioning
confidence: 64%
“…In the present study, bud regeneration rate was generally low. Paluku et al [19] made the same observations during in vitro regeneration of Cola acuminata. This study revealed that the production of friable, greenish callus in the two local varieties tested auguring a prospect for intense proliferation through regeneration of neoformed organogenesis callus.…”
Section: Discussionmentioning
confidence: 64%
“…In Côte d'Ivoire, leafy greenwood and softwood stem cuttings of G. kola presented good ability to shooting and rooting in non-mist propagators while leafless hardwood stem cuttings were only able to shoot even without application of exogenous hormones [363,364]. In the Democratic Republic of Congo, leafy stem cuttings of C. acuminata with 25 cm 2 leaves rooted well (81%) when treated with the auxin Indol-butyric acid [366]. In the difficult to propagate A. floribunda, like Cola anomala, rooting was significantly improved with an application of nitrogen-based fertilisers [150,362].…”
Section: Vegetative Propagationmentioning
confidence: 99%
“…Avec le colatier, Cola acuminata, des taux supérieurs à 80% ont été obtenus par une multiplication végétative par bouturage. (Paluku et al, 2018) Selon Barbier (2012, Jatropha curcas L. est capable de résister à une saison sèche plus ou moins prononcée avec des températures moyennes variant de 20 °C à 32 °C. Son tronc à caudex qui constitue un réservoir d'eau, est capable de résister à des périodes de sécheresse prolongées (Formad environement, 2013).…”
Section: Le Débourrement Des Boutures Le Mode De Conservation Sur Le unclassified